Hiding in Plain Sight: Higher Education Pink and Blue Collar Staff Experiences as Returning Adult Learners, Workers, and Family Members - Susan J. Bracken; Jeanie K. Allen (Adult Education Research Conference, 2006)
This study focuses upon a sometimes invisible subset of adult learners: higher education staff members. The participant interviews are part of a pilot study intended to create increased understanding of how these unique adult learners experience their environments. This paper focuses upon one central work/school theme, ‘knowing your place’.
Keywords: Adult learners; higher education; higher education staff